Assessing the Role of Nrf2/GPX4-Mediated Oxidative Stress in Arsenic-Induced Liver Damage and the Potential Application Value of Rosa roxburghii Tratt [Rosaceae]. (25th April 2022) - Xu, Yuyan; Zeng, Qibing; Sun, Baofei; Wei, Shaofeng; Wang, Qingling; Zhang, Aihua
Abstract : Arsenic poisoning is a geochemical disease that seriously endangers human health. The liver is one of the important target organs for arsenic poisoning, several studies have shown that oxidative stress plays an important role in arsenic-induced liver damage. However, the specific mechanism of arsenic-induced oxidative stress has not yet been fully elucidated, and currently, there are no effective intervention measures for the prevention and treatment of arsenic-induced liver damage. In this study, the effect of the Nrf2/GPX4 signaling pathway and oxidative stress in the arsenic-induced liver damage was first evaluated. The results show that arsenic can activate the Nrf2/GPX4 signaling pathway and increase the oxidative stress, which in turn promotes arsenic-induced liver damage in MIHA cells. Moreover, when we applied the Nrf2 inhibitor, the promoting effect of arsenic on liver damage was alleviated by inhibiting the activation of the Nrf2/GPX4 signaling pathway. Subsequently, the Rosa roxburghii Tratt [Rosaceae] (RRT) intervention experiments in cells and arsenic poisoning population were designed. The results revealed that RRT can inhibit Nrf2/GPX4 signaling pathway to reduce oxidative stress, thereby alleviates arsenic-induced liver damage. This study provides some limited evidence that arsenite can activate Nrf2/GPX4 signaling pathway to induce oxidative stress, which in turn promotes arsenic-induced liver damage in MIHA cells. The second major finding was that Kaji-ichigoside F1 may be a potential bioactive compound of RRT, which can inhibit Nrf2/GPX4 signaling pathway to reduce oxidative stress, thereby alleviates arsenic-induced liver damage. Our study will contribute to a deeper understanding of the mechanisms in arsenic-induced liver damage, these findings will identify a possible natural medicinal food dual-purpose fruit, RRT, as a more effective prevention and control strategies for arsenic poisoning.